1978
DOI: 10.1002/jcp.1040940212
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of protein synthesis in human diploid fibroblasts: Reduced initiation efficiency in resting cultures

Abstract: The level of poly A+ RNA in growing cultures of human diploid fibroblasts is 1.8-fold times greater than in resting cultures. The level of functional ribosomes in growing cultures is 2.8 times that in resting cultures. Since transit times are similar in both types of cells, it can be concluded that the rate of protein synthesis in growing cultures is 2.8 times that in resting cultures. a reduced efficiency of mRNA translation at the level of initiation in resting cultures is proposed as a probable explanation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…We observed a dramatic decrease in levels of critical translation factors during cellular transition from dividing state to quiescence, suggesting that their cleavage by proteasomes can contribute to a well-known phenomenon of translational attenuation in resting/quiescent cells 42. A broader question is how the IPDP regulates levels of different IPSes at distinct stages of cell life.…”
Section: Discussionmentioning
confidence: 86%
“…We observed a dramatic decrease in levels of critical translation factors during cellular transition from dividing state to quiescence, suggesting that their cleavage by proteasomes can contribute to a well-known phenomenon of translational attenuation in resting/quiescent cells 42. A broader question is how the IPDP regulates levels of different IPSes at distinct stages of cell life.…”
Section: Discussionmentioning
confidence: 86%
“…A number of additional parallels can be drawn between senescence and the Go state produced in young cells by confluence or serum deprivation. Similarities between these two noncycling states have been demonstrated with respect to decreases in the template activity of the nuclei (Rossini et al, 1976), decreased RNA and protein synthesis (Evans et al, 1978;Meedel and Levine, 1978;Macieira-Coelho et al, 1966), increases in protein degradation (Castor, 1977;Bradley et al, 1976), and increases in mean cell volumes (Mitsui and Schneider, 1976). Furthermore, Rabinovitch and Norwood (1980) and Stein and Yanishevsky (1981) have shown that senescent HDFL cells and quiescent (serumdeprived) cells at low passage levels behave in a similar manner upon fusion with cycling HDFL cells.…”
mentioning
confidence: 91%
“…Serum factor depletion (Meedel and Levine, 1978), heat shock (Scharf and Nover, 1982) and hyperosmolarity (Kruppa and Martini, 1978;Martini and Kruppa, 1979) on the other hand reduce protein synthetic activity by affecting initiation rates as well as reducing the fraction of mRNAs in polysomes. These treatments lead in addition to a massive dephosphorylation of protein S6 (Kruppa and Martini, 1978;Scharf and Nover, 1982).…”
Section: Introductionmentioning
confidence: 99%